ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB), SERVICE QUALITY, AND PATIENT SATISFACTION: A CASE STUDY OF THE NURSES IN PRIVATE HOSPITALS OF SURABAYA - Thomas Stefanus Kaihatu; Sundring Pantja Djati (MIX: JURNAL ILMIAH MANAJEMEN, 2016)
Abstract. As a distinctive employee behavior, organizational citizenship behavior(OCB) plays an important role in shaping the quality of service provided by nurses tofurther enhance the feeling of satisfaction experienced by customers. This researchaims to explain the relationship between OCB, service quality, and patient satisfactionin hospital setting. We use the perception of costumers in explaining the threeconstructs used in this research. The respondents are 30 full time nurses and 100hospital inpatients of private hospitals (63.29% response rate) in private hospitals inSurabaya. SEM-PLS is used for the data analysis, yielding results that OCB haspositive and significant relationship towards service quality, and service quality haspositive and significant relationship towards customer satisfaction. Thus, the resultsconfirm previous researchers’ findings. Future research direction is advised as therelationship between service quality and customer satisfaction is found to besignificantly weaker than previous researchers’ results.Keyword: Organizational citizenship behavior, service quality, customer satisfactionAbstrak. Sebagai sebuah perilaku karyawan yang unik, organizational citizenshipbehavior (OCB) memegang peranan penting dalam membentuk kualitas layanan sustersusterdi Rumah Sakit yang nantinya akan meningkatkan kepuasan konsumen.Penelitian ini bertujuan untuk menjelaskan hubungan antara OCB, kualitas layanan,dan kepuasan konsumen di setting Rumah Sakit. Persepsi konsumen digunakan dalammenjelaskan ketiga konstruk dalam penelitian ini. Responden berjumlah 30 suster yangbekerja penuh waktu dan 100 pasien rumah sakit swasta (63,29% tingkat respon) diSurabaya. SEM-PLS digunakan untuk menganalisa data, dengan hasil bahwa OCBmemiliki pengaruh positif dan signifikan terhadap kualitas layanan, dan kualitaslayanan berpengaruh positif signifikan terhadap kepuasan pelanggan. Hasil inimengkonfirmasi penelitian-penelitian terdahulu. Saran untuk penelitian selanjutnyadijelaskan lebih lanjut karena hubungan kualitas layanan dan kepuasan pelangganditemukan jauh lebih lemah daripada hasil peneliti-peneliti terdahulu.